Proceedings of the ACM Symposium on Applied Perception 2012
DOI: 10.1145/2338676.2338683
|View full text |Cite
|
Sign up to set email alerts
|

How responsiveness affects players' perception in digital games

Abstract: Digital games with realistic virtual characters have become very popular. The ability for players to promptly control their character is a crucial feature of these types of games, be it platform games, first-person shooters, or role-playing games. Controller latencies, meaning delays in the responsiveness of a player's character, for example due to extensive computations or to network latencies, can considerably reduce the player's enjoyment of a game. In this paper, we present a thorough analysis of the conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Studies involving different setups and sensorimotor tasks come to different conclusions when investigating the perceptual threshold for delay detection. Users might be unaware of delays below 120 ms [Mauve et al 2004], or below 150 ms when controlling characters in computer games [Jörg et al 2012]. Even delays around 200 ms between mouse movements and cursor movements or between a button press and a visual stimulus might go unnoticed [Raaen et al 2014;Rohde et al 2014a].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies involving different setups and sensorimotor tasks come to different conclusions when investigating the perceptual threshold for delay detection. Users might be unaware of delays below 120 ms [Mauve et al 2004], or below 150 ms when controlling characters in computer games [Jörg et al 2012]. Even delays around 200 ms between mouse movements and cursor movements or between a button press and a visual stimulus might go unnoticed [Raaen et al 2014;Rohde et al 2014a].…”
Section: Related Workmentioning
confidence: 99%
“…This holds especially for applications in which users obtain real-time feedback of their action, as is the case when they are presented with their own avatar. In setups presenting delayed visual feedback with respect to motor performance, high latencies influence perceived temporal coherence of the scene, sense of agency, sense of ownership, as well as motor performance [Franck et al 2001;Longo and Haggard 2009;Jörg et al 2012;Imaizumi and Asai 2015]. If we had knowledge on which duration of latencies is still acceptable with respect to these factors, we would be able to design systems that reduce the risk of suffering from latency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature suggests values of 150 ms for controlling characters in computer games, since higher latencies are already directly noticeable for untrained users and affect players in several ways [Jörg et al 2012]. Meehan et al [2003] showed that decreasing the latency from 90 ms to 50 ms already affects presence in virtual environments.…”
Section: R2: Low Latency and High Frame Ratementioning
confidence: 99%
“…High latency causes in fact system feedback to lag behind user actions and thus significantly degrades the interactivity of the user experience. Therefore, several approaches were proposed so as to reliably recognize actions with minimal latency [4,21,3,22,23,24]. Ellis et al [3] proposed new algorithms for reducing latency for both presegmented and online action classification tasks.…”
Section: Related Workmentioning
confidence: 99%